Reasons for the low bacteriological coverage of tuberculosis reported in Mpumalanga Province, South Africa - Mngomezulu, N. (Public Health Action, 2015)
Setting: Public sector hospitals and primary health clinics in the Mpumalanga Province of South Africa. Objective: To determine whether failure to adhere to tuberculosis (TB) diagnostic guidelines (i.e., submit sputum for smear microscopy) contributed to the low bacteriological coverage reported for TB in 2008 in Mpumalanga Province. Methods: We reviewed clinical records for new pulmonary TB cases at 30 of 118 randomly selected facilities that met the bacteriological coverage target of 80% and 30/87 facilities that did not. Data for hospital and clinic cases were abstracted into case report forms, captured electronically and compared with data from the electronic TB register (ETR). We assessed age, sex, human immunodeficiency virus (HIV) infection and facility type as potential confounders for recording of smear microscopy results. Results: Age, sex and HIV infection did not influence recording of results. In hospitals, 61.8% of pulmonary TB cases had sputum smear results in their clinical records compared to 93.6% at clinics (P < 0.001). Of the 711 cases (30.3%) that did not have smear results in the ETR, 342 (48.1%) did have smear results in their clinical records. Conclusion: Both poor clinical practice (especially in hospitals) and poor record keeping have contributed to the low bacteriological coverage reported. These shortcomings need to be addressed to improve patient care and programme management.